STUDI SURVEI LATIHAN LADDER DRILL TERHADAP KEMAMPUAN MENGGIRING BOLA PADA PEMAIN EKSTRAKURIKULER FUTSAL DI MA AL-IBROHIMY - Mohammad Nor Abdul Azis; Haryo Mukti Widodo; Agus Himawan; Septyaningrum Putri Purwoto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to determine the futsal ball dribbling ability after implementing ladder drill training on futsal extracurricular students at Ma Al-Ibrohimy. The method used in this research was a survey, with a sample of 19 futsal extracurricular students, using the Quota Sampling technique. The instrument of this research is a futsal ball dribbling test to measure dribbling ability. The results showed that the lowest dribbling score was 9 and the highest score was 16. The calculated average value (M) was 11.59 with a standard deviation of 2.209. The conclusion of this research shows that the survey results analyzed using SPSS have a good score distribution. By implementing the right treatment, it is possible that dribbling results will increase compared to the values ​​obtained during the survey.